Proliferative arteriopathy of the nasal philtrum in two Brazilian Mastiff dogs - Ferreira, Ana Paula C.; Grandi, Fabrizio (Brazilian Journal of Veterinary Pathology, 2017)
Proliferative arteritis of the canine nasal philtrum is an unusual disease with an unknown etiology and very few cases described in literature to date. Two patients with characteristic lesions underwent biopsy and confirmation by histopathological assessment. The first case was treated with oral prednisolone once daily and topical tacrolimus twice daily. The second case was treated twice daily with pentoxifylline and topical tacrolimus. Both treatments were successfully used by other authors previously. In result, clinical improvement varied among patients. The lesion of the first case showed no clinical improvement after 15 days of treatment. The second case showed a mild improvement of the initial lesion. In conclusion, treatment with tracolimus, pentoxifylline, and prednisonole appears to have a good effect in mild and early lesions. The objective of this paper was to describe the clinical findings, treatment options and histopathological aspects in two Brazilian Mastiff dogs, not previously reported.